If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(5z-(3))-(4(2z+1))=5z-(2)
We move all terms to the left:
3(5z-(3))-(4(2z+1))-(5z-(2))=0
We multiply parentheses
15z-(4(2z+1))-(5z-2)-9=0
We get rid of parentheses
15z-(4(2z+1))-5z+2-9=0
We calculate terms in parentheses: -(4(2z+1)), so:We add all the numbers together, and all the variables
4(2z+1)
We multiply parentheses
8z+4
Back to the equation:
-(8z+4)
10z-(8z+4)-7=0
We get rid of parentheses
10z-8z-4-7=0
We add all the numbers together, and all the variables
2z-11=0
We move all terms containing z to the left, all other terms to the right
2z=11
z=11/2
z=5+1/2
| 2(2y-4)+12=-y+8+5y | | F(x)=x5+5x | | (5.15-2x)x(7.65-x)=0 | | 1/2(3x+4)=3+2 | | 6x-3(x-5)=-(2x+15) | | -4(2n-5=-28 | | 5(3-d)=2+1 | | 9/8=3w/24 | | 12x^2-10x-28=0 | | 28+8x=8(x+3) | | x^(2/3)+9x^(1/3)+8=0 | | -9/8=3w/24 | | 23=3n-7 | | 2x2−40x+200=0 | | F(x)=x3+5x | | 4/3=16/b | | 6=2x+3/5 | | 36=-3(2x-4) | | -17+x+23=-4 | | b/13-8b/13=21/13 | | 4n-15=-4n | | 3/5x-15=6/5x12 | | 4n-15=4n | | 2r+8/4=5r-10/5 | | 27×3x=32x+5 | | 1/3-x/3=8/3 | | 3x(x-3)+5(x+7)-x(x+1)-2(x2+7)+4=0 | | |x-5|=|x-11| | | -|-3p|p=10 | | 2.1=3.1-0.5x | | 2x+(x-8)=x-36 | | 12x-4=-8+8x |